FEATURES OUTPUT FIRMS IN INTERNATIONAL MARKETS - ZAKRYZHEVSKA, IRYNA; POLOZOVA, VALENTYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the main components of the company’s entry into the foreign market, important aspects of foreign economic activity of firms: the main motives and strategies of enterprises, as well as barriers that prevent enterprises from entering the international arena. The company’s entry into foreign markets, where fierce competition prevails, is possible only with the use of modern management methods and modern methods of market penetration. The international market is extremely capacious, which creates significant prospects for enterprises, but at the same time makes additional demands on management. Enterprise policy requires a specific approach to maintaining the competitiveness of products and firms directly, both in quantitative and qualitative terms and more careful adherence to the principles and methods of marketing. In the context of globalization, foreign economic activity is a major component of the evolutionary development of the enterprise. For a long time, the economic literature has held the view that globalization is one of the strategies of enterprises aimed at conquering foreign markets. As for Ukrainian enterprises, unfortunately, in most cases, at the beginning of foreign economic activity, strategic management methods were rarely used. The main motivating motive for entering foreign markets was curiosity. The primary goals, such as direct entry into international markets, have been achieved by enterprises. The question arises, what to do next? A number of Ukrainian enterprises already operating in foreign markets are facing the problem of either expanding their foreign economic activity or, conversely, reducing it. The answer to this question depends on what goals the company set for itself at the stage of entering its products on international markets, which strategy was chosen as the primary one. Before forming a strategy for the development of foreign economic activity and its implementation, it is necessary to evaluate the existing strategy. This is necessary because it is impossible to plan for the future without having a clear idea of the state of the organization and what strategies it implements.